Pelaksanaan Cuti Bersyarat Bagi Remaja Di Lembaga Pemasyarakatan Wanita Kelas II B Bengkulu - Sachi Jeni Utari (Jurnal Terekam Jejak, 2024)
Nowadays, violations of the law or criminal acts are not only committed by adults but criminal acts are increasingly being committed by children. When carrying out their criminal period, children have certain rights, one of which is the right to obtain Conditional Leave. Conditional leave is a coaching program to integrate prisoners and children into community life after meeting predetermined requirements. This study aims to determine the implementation of Conditional Leave for juvenile in Women's correctional institution Class II B Bengkulu. This research uses a normative-empirical method. The result of this research is that the Women's correctional institution Class IIB Bengkulu has been guided by the Minister of Law and Human Rights Regulation Number 7 of 2022 regarding the granting of Conditional Leave for Juvenile but there are obstacles in this process. Based on the conclusion of this research, it is necessary to improve cooperation, coordination and supervision in the implementation of the proposal and socialization to the family.